The Effect of Occupational Visas on Native Employment: Evidence from Labor Supply to Farm Jobs in the Great Recession - Michael A. Clemens (Institute of Labor Economics (IZA), 2017)
The effect of foreign labor on native employment within an occupation depends on native labor supply to that occupation which is rarely directly measured even if native and foreign labor are perfect substitutes in production. This paper uses two natural quasi-experiments to directly compare foreign to native labor supply in manual farm work. The first quasi-experiment is a legal requirement for employers to demand native labor with infinite elasticity at the wage earned by migrants; the second is a large exogenous shock to native workers' reserve option. Together these offer what is essentially a natural audit study in which tens of thousands of 'immigrant jobs' were offered to native workers with a range of exogenously varying terms. It uses novel data on the universe of domestic applicants to tens of thousands of farm jobs in the state of North Carolina over a 15 year period. The wage elasticity of unemployed domestic workers' relative labor supply is 0.0015. This implies that the effect of migrant labor supply on native employment is close to zero within this occupation, and may be positive outside it. Job-specific estimates of this kind are useful alongside more generalized evaluations of immigration because immigration policy often regulates access to specific occupations.
Keywords: F22; J61; O15; 330; natural experiment; agriculture; farm; wage; employment; labor-market; visa; displacement; immigration; immigrant; United States; Mexico